Knockdown of anion exchanger 2 suppressed the growth of ovarian cancer cells via mTOR/p70S6K1 signaling - Li-Jun Zhang (Nature Portfolio, 2017)
Abstract Anion exchanger 2 (AE2, encoded by SLC4A2) is a sodium-independent chloride/bicarbonate transporter and implicated in the regulation of intracellular pH and membrane potential. Previous studies have linked AE2 to the tumorigenesis of various cancers. Here, AE2 was identified as an up-regulated protein in ovarian cancer tissues compared to adjacent non-tumor lesions based on quantitative proteomics analysis. AE2 mRNA was also overexpressed in human ovarian cancer samples, and that AE2 overexpression correlated with the shortened survival time of ovarian cancer patients. Short-hairpin RNA-mediated knockdown of AE2 in A2780 and SK-OV-R3 cells inhibited cell growth and induced cell cycle G1 phase arrest. In nude mice, its stable knockdown inhibited the tumorigenicity of A2780 cells. Gene set enrichment analysis on The Cancer Genome Atlas dataset identified that the cell cycle process and mTOR pathway were correlatively with the AE2 expression. Expression of key regulators of G1/S transition (Cyclin D1 and CDK4), and phosphorylation levels of p70S6K were notably reduced in AE2 knockdown cells. Moreover, experiments with mTOR inhibitor suggested that AE2 may promote cell cycle progression through mTOR/p70S6K1 pathway. Together, our results suggest up-regulated AE2 promotes ovarian cancer tumorigenesis by activating mTOR/p70S6K1 pathway and implicate the potential application of AE2 in cancer therapy.